2015
DOI: 10.1155/2015/451512
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Regulates Neurogenesis in the Hippocampus following Seizures

Abstract: Hippocampal neurogenesis is changed by brain injury. When neuroinflammation accompanies injury, activation of resident microglial cells promotes the release of inflammatory cytokines and reactive oxygen/nitrogen species like nitric oxide (NO). In these conditions, NO promotes proliferation of neural stem cells (NSC) in the hippocampus. However, little is known about the role of NO in the survival and differentiation of newborn cells in the injured dentate gyrus. Here we investigated the role of NO following se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Neuronal and glial cells interact with each other to maintain the brain homeostasis and integrate to promote the neurogenesis and memory processes [ 3 5 ]. Normally, glial cells exist in resting state, but under stress or pathological conditions, they become activated and increase the release of the pro-inflammatory molecules causing neuroinflammation that is detrimental to neurogenesis and further impair spatial memory [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal and glial cells interact with each other to maintain the brain homeostasis and integrate to promote the neurogenesis and memory processes [ 3 5 ]. Normally, glial cells exist in resting state, but under stress or pathological conditions, they become activated and increase the release of the pro-inflammatory molecules causing neuroinflammation that is detrimental to neurogenesis and further impair spatial memory [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, evidence of increased cell proliferation has also been observed in the hippocampus of patients with temporal lobe epilepsy (Blümcke et al, 2001 ; Crespel et al, 2005 ). In the model used by our group, the peak of cell proliferation in the DG was shown to occur on day 5 after seizure induction, with a significant increase in neuroblast migration after 14 days (Carreira et al, 2015 ), results that we were able to replicate in the present work. This heavy enhancement of early neurogenesis indicates that the microenvironment in the hippocampus not long after seizures is extremely pro-neurogenic, which makes it difficult for changes due to altered levels of calpain activity to be observed.…”
Section: Discussionsupporting
confidence: 78%
“…The KA model of brain lesion is thus often used for research involving hippocampal damage, especially in studies of temporal lobe epilepsy (Levesque and Avoli, 2013 ). It is also a good model for investigating hippocampal injury and its consequences (Araújo et al, 2008 ; Carreira et al, 2010 , 2015 ). Since the hippocampus is the main structure involved in learning and memory, it is not surprising that treatment with KA in rodents can induce cognitive impairment (Stubley-Weatherly et al, 1996 ), which has also been reported in patients with temporal lobe epilepsy (Hattiangady and Shetty, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations